(untitled) (Academicia Globe: Inderscience Research, 2024)
The article examines the role and significance of the investment strategy in the overall development strategy of enterprises, analyzes the main goals and principles of developing an enterprise investment strategy, and also discusses conclusions and recommendations based on international experience.